2014
DOI: 10.5530/ijper.47.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Development and Physicochemical, In Vitro and In Vivo Evaluation of Transdermal Patches of Zaleplon

Abstract: A series of potential bioactive compounds, 4-Amino-5-mercapto-3-(4-chlorophenyl)-1, 2, 4-triazole (1d), 4-Amino-5-mercapto-3-(4-nitrophenyl)-1, 2, 4-triazole (2d) , 4-Amino-5-mercapto-3-(2, 4-dichlorophenyl)-1, 2, 4-triazole (3d), 4-Amino-5-mercapto-3-(2-chlorophenyl)-1, 2, 4-triazole (4d), 4-Amino-5-mercapto-3-(2-methylphenyl)-1, 2, 4-triazole (5d), 4-Amino-5-mercapto-, 2, 4-triazole (6d) were synthesized according to the 1 literature methods. The synthesized compounds were characterized by FT-IR, H NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The average skin irritation index was calculated to be 0. From the results, it can be concluded that curcumin nanocrystal gel was found to be irritation-free, like the marketed formulation (Povidone ointment) [49].…”
Section: In Vivo Skin Irritability Studymentioning
confidence: 90%
“…The average skin irritation index was calculated to be 0. From the results, it can be concluded that curcumin nanocrystal gel was found to be irritation-free, like the marketed formulation (Povidone ointment) [49].…”
Section: In Vivo Skin Irritability Studymentioning
confidence: 90%
“…All the formulated mucoadhesive patches were observed for physical appearances i.e., shape, thickness etc. (Tirunagari et al 2014).…”
Section: Evaluation Physical Appearancementioning
confidence: 99%
“…12 Moreover, it is an adhesive patch and offers a promising approach for developing a topical route to give local or systemic effects. 13 Advances in the field of adhesive science have paved way for developing optimized delivery systems which are capable of providing adequate skin adhesion, accommodate high drug load and greater drug delivery.…”
mentioning
confidence: 99%